Scenario-Based Life Cycle Assessment of Downstream Hazardous Wastewater Treatment for Environmental Impact Reduction - Assyfa Sopyasari; Titi Tiara Anasstasia; Novianty (Indonesian Journal of Environmental Management and Sustainability, 2026)
The rapid growth of industry in Indonesia has led to an increase in Hazardous and Toxic Waste (B3), including liquid waste with complex chemical characteristics that pose high environmental risks. Treatment facilities for B3 wastewater can generate significant impacts such as Global Warming Potential (GWP), Human Toxicity Potential (HTP), and Freshwater Aquatic Ecotoxicity Potential (FAETP). This study evaluates the implementation of treated water recycling using the Life Cycle Assessment (LCA) method with the CML-IA Baseline approach. The functional unit applied was 1 m3 of treated wastewater. Results show that under the baseline scenario, GWP reached 102.89 kg CO2 eq, HTP 62.92 kg 1,4 DB eq, and FAETP 10.11 kg 1,4-DB eq. Applying recycling scenarios of 30%; 50%; and 80% consistently reduced impacts across all categories. Each 10% increase in recycling volume reduced environmental burdens by approximately 10%. These findings highlight recycling as an effective and measurable strategy to reduce environmental impacts while supporting sustainable production and consumption principles.